2003
DOI: 10.1128/ec.2.4.809-820.2003
|View full text |Cite
|
Sign up to set email alerts
|

POS5 Gene of Saccharomyces cerevisiae Encodes a Mitochondrial NADH Kinase Required for Stability of Mitochondrial DNA

Abstract: In a search for nuclear genes that affect mutagenesis of mitochondrial DNA in Saccharomyces cerevisiae, an ATP-NAD (NADH) kinase, encoded by POS5, that functions exclusively in mitochondria was identified. The POS5 gene product was overproduced in Escherichia coli and purified without a mitochondrial targeting sequence. A direct biochemical assay demonstrated that the POS5 gene product utilizes ATP to phosphorylate both NADH and NAD ؉ , with a twofold preference for NADH. Disruption of POS5 increased minus-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
139
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 86 publications
3
139
1
Order By: Relevance
“…4B). Since NADPH is used as a cofactor by enzymes involved in the detoxification of peroxide, superoxide, and hydroxyl radicals that are generated in mitochondria (48 -50), depletion of the mitochondrial NADPH pool would be expected to lead to an increased level of oxidative damage to mitochondrial proteins and DNA, consistent with the mitochondrial genome instability that results from pos5 mutation (2). In contrast to the respiratory incompetence of pos5 mutants, utr1 mutants displayed wild-type growth on glycerol (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4B). Since NADPH is used as a cofactor by enzymes involved in the detoxification of peroxide, superoxide, and hydroxyl radicals that are generated in mitochondria (48 -50), depletion of the mitochondrial NADPH pool would be expected to lead to an increased level of oxidative damage to mitochondrial proteins and DNA, consistent with the mitochondrial genome instability that results from pos5 mutation (2). In contrast to the respiratory incompetence of pos5 mutants, utr1 mutants displayed wild-type growth on glycerol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, transforming freshly prepared pos5 mutants with a POS5 plasmid restores resistance to reactive oxygen species and growth on nonfermentable carbon sources, but older pos5 mutants lose the ability to have their respiratory defect restored by Pos5 expression. These data suggest that mitochondrial NADPH-dependent antioxidant reductases are required to protect mitochondria from reactive oxygen species damage and that this damage can lead to irreparable lesions to the mitochondrial genome (1,2). In the cytosol, NADP is used by pentose phosphate pathway enzymes glucose-6-phosphate dehydrogenase Zwf1 and 6-phosphogluconate dehydrogenase Gnd1 and -2 to produce ribulose-5-phosphate and NADPH (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Binary sequence alignments of NADK3 revealed negligible similarity to either of the previously identified Arabidopsis NADKs. However, sequence analysis revealed that NADK3 possessed similarity to POS5 (YPL 188W) from yeast (S. cerevisiae), recently shown to be an NADHK [13,14]. This enzyme, which to date has only been described in yeast, is distinct from NADK [15,16] and localizes to the mitochondria [13,14,17].…”
Section: Introductionmentioning
confidence: 99%